TRANSFORMASI PEMBELAJARAN IPAS DI ERA DIGITAL MELALUI PENDEKATAAN DEEP LEARNING UNTUK MENINGKATKAN LITERASI SAINS DAN KEMANDIRIAN BELAJAR SISWA - Asih, Tri Unggul Sari; Rohman, Akhmad Dalil; Prasetiya, Uki Adi; Mahmudah, Umi (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The transformation of education in the digital era requires IPAS learning in elementary schools to move beyond conventional approaches and to foster students’ scientific literacy, critical thinking, and learning independence as essential 21st-century competencies. However, various reports and research findings indicate that the scientific literacy of Indonesian elementary school students remains relatively low, while classroom learning practices are still dominated by lecturing and rote memorization with limited and suboptimal use of technology. This condition highlights the need for more meaningful, contextual, and student-centered learning approaches. This study focuses on examining the application of the Deep Learning approach in IPAS learning as a strategy to enhance scientific literacy and learning independence among elementary school students. The study employed a library research method with a qualitative approach, involving the identification, selection, and analysis of various literature sources, including books, national and international journal articles, and relevant research reports published over the past ten years. Data analysis was conducted using content analysis techniques to identify patterns, concepts, and key findings related to Deep Learning, scientific literacy, and learning independence. The results indicate that the Deep Learning approach, implemented through problem-based learning, inquiry-based learning, project-based learning, and blended learning strategies supported by interactive digital media, has the potential to increase student engagement, understanding of scientific concepts, the ability to analyze scientific phenomena, and learning independence. The findings conclude that the Deep Learning approach is relevant and has strong potential for implementation in elementary school IPAS learning, provided that it is supported by teacher readiness, adequate facilities and infrastructure, and systematic instructional planning to ensure optimal impact on improving students’ scientific literacy and learning independence. ABSTRAK Transformasi pendidikan di era digital menuntut pembelajaran IPAS di sekolah dasar tidak lagi bersifat konvensional, tetapi mampu mengembangkan literasi sains, berpikir kritis, dan kemandirian belajar siswa sebagai kompetensi abad ke-21. Namun, berbagai laporan dan hasil penelitian menunjukkan bahwa literasi sains siswa sekolah dasar di Indonesia masih relatif rendah, sementara praktik pembelajaran di kelas masih didominasi metode ceramah dan hafalan dengan pemanfaatan teknologi yang belum optimal. Kondisi ini menunjukkan perlunya pendekatan pembelajaran yang lebih bermakna, kontekstual, dan berpusat pada siswa. Penelitian ini berfokus pada kajian penerapan pendekatan Deep Learning dalam pembelajaran IPAS sebagai strategi untuk meningkatkan literasi sains dan kemandirian belajar siswa sekolah dasar. Penelitian ini menggunakan metode library research dengan pendekatan kualitatif, melalui penelusuran, seleksi, dan analisis berbagai sumber pustaka berupa buku, artikel jurnal nasional dan internasional, serta laporan penelitian yang relevan dan dipublikasikan dalam sepuluh tahun terakhir. Analisis data dilakukan menggunakan teknik analisis isi untuk mengidentifikasi pola, konsep, dan temuan utama terkait Deep Learning, literasi sains, dan kemandirian belajar. Hasil kajian menunjukkan bahwa pendekatan Deep Learning, melalui strategi problem-based learning, inquiry-based learning, project-based learning, dan blended learning yang didukung media digital interaktif, berpotensi meningkatkan keterlibatan siswa, pemahaman konsep sains, kemampuan analisis fenomena ilmiah, serta kemandirian belajar. Simpulan penelitian ini menegaskan bahwa pendekatan Deep Learning relevan dan potensial diterapkan dalam pembelajaran IPAS di sekolah dasar, dengan catatan diperlukan kesiapan guru, dukungan sarana prasarana, serta perencanaan pembelajaran yang sistematis agar implementasinya memberikan dampak optimal terhadap peningkatan literasi sains dan kemandirian belajar siswa.